Substance and Style in the Prolife Discourse - Daniel Daly (Journal of Moral Theology, 2023)
This essay is directed to the prolife community and argues that the abortion discourse on Catholic campuses will be improved significantly if the prolife community more intentionally integrates specific substantive and stylistic changes regarding the ethics and politics of abortion. Substantively, the impasse in the discourse may be initially bridged by what many prolife and prochoice persons should generally agree on—that abortion is driven by vicious social structures and a broken moral culture. Abortion is primarily a socially-generated moral problem that requires a socially-generated moral solution. The prolife and prochoice communities can agree and potentially collaborate on solutions to this social crisis. In light of the social factors that drive abortion, the prolife community should take seriously the experiences of women who have abortions and express more compassion for them. This community all too often quickly dismisses the suffering of women and, instead, trains its attention nearly exclusively on the unborn child. Both the mother and unborn child are victims of injustice and are deserving of compassion and mercy. Stylistically, the mode of the prolife discourse should reflect its message. A message of charity for all persons should be communicated charitably. Dialoguing with love is opposed to the ‘culture warrior’ ethos that currently plagues our nation.